(untitled) - Fazekas, Miroslav; Sulgan, Marian (Doprava a spoje, 2012)
In the case of unintended formation of the incident consequences train accidents in freight rail will be significant property damage, but the passenger transport in rail accident it is much more serious because in addition to physical damage can compromise the health and lives of people.